The Action of inVestigational Drugs of Brucella abortus in the L- and S-forms on the Subpopulations of Blood Cells and Peritoneal Fluid of White Mice (Communication 2) - S. A. Vityazeva; T. P. Starovoitova; V. I. Dubrovina; L. M. Mikhailov; K. Yu. Yastremskaya; L. E. Tokareva; N. L. Barannikova; S. V. Balakhonov (Эпидемиология и вакцинопрофилактика, 2015)
We have estimated the effects of the Brucella abortus 19 ВА inactivated vaccine, thermo extracts of Brucella abortus I-206 in the L- and S-forms and corpuscular antigen of Brucella abortus I-206 in L-form on the population and subpopulation structure of blood cells and peritoneal fluid of white mice. It was showed that the antigen preparations of Brucella abortus I-206 in L-form didn't caused endogenous intoxication of the organism of experimental animals in distinction from the inactivated vaccine of Brucella abortus 19 BA.